Penguatan Kapasitas Petani Melalui Sosialisasi Kemitraan Usaha Agribisnis Jagung di Kabupaten Pidie - rika, safrika (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
Pidie Regency has significant land potential to become a corn production center, but farmers often face obstacles in capital, technology, and market access. This community service activity aims to provide understanding to farmers regarding the importance of agribusiness partnerships to increase income and farming independence. The method of implementation was carried out through counseling and socialization on principles, legal bases, and partnership patterns to farmer groups. The material presented covered the urgency of partnerships, the legal framework, and strategies to overcome obstacles in partnerships. The results of the activity showed an increase in farmers' insight regarding rights and obligations in written partnership agreements and awareness of the importance of transparent business management. It is hoped that through this understanding, farmers can build a stronger bargaining position and avoid cooperation failures due to weak rules or management.